Resin material and preparation method thereof, preparation method of resin wafer and optical product

By reasonably proportioning cycloolefin copolymers, inorganic nanoparticles, antioxidants and toughening agents in resin materials, the problem of low refractive index of existing resin materials is solved, and resin materials with high refractive index and stable performance are achieved, meeting the needs of the AR field.

CN119613907APending Publication Date: 2025-03-14GOERTEK OPTICAL TECHNOLOGY (QINGDAO) CO LTD

Patent Information

Application Number
CN202411586906.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The refractive index of existing resin materials is usually not high, making it difficult to meet the demand for high refractive index in the field of augmented reality (AR). At the same time, the material properties are unstable and the preparation process is complex.

Method used

By reasonably proportioning cycloolefin copolymers, inorganic nanoparticles, antioxidants and toughening agents, resin materials with refractive index greater than 1.7 were prepared, and specific preparation methods were adopted to ensure the stability and processing performance of the material.

Benefits of technology

It achieves a high refractive index of resin materials, meets the needs of the AR field, and ensures the stable performance and good processing performance of the materials, reduces costs and enhances the market competitiveness of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The embodiment of the invention provides a resin material and a preparation method thereof, a preparation method of a resin wafer and an optical product. Wherein the resin material is a composition and comprises the following components in parts by weight: 100 to 120 parts of cycloolefin copolymer, 50 to 200 parts of inorganic nanoparticles, 0.1 to 1 part of antioxidant and 1 to 20 parts of flexibilizer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of cyclic olefin copolymers. Specifically, the embodiments of the present application relate to a resin material, a method for preparing a resin material, a method for preparing a resin wafer, an optical product, and an electronic device. Background Art

[0002] In the field of augmented reality (AR) diffraction optical waveguides, for example, the choice of wafer material is crucial to achieving high refractive index requirements. At present, due to the need for high refractive index, wafer materials are still mainly glass. However, glass is brittle and fragile, and has high density and heavy weight, which not only increases the cost, but also makes it difficult to achieve the demand for lightweight products. Therefore, resin wafers, as a future development direction, have broad application prospects. However, the refractive index of traditional resin materials is usually not high. In order to meet the application requirements of the AR field, the refractive index of the resin material needs to be increased to above 1.7.

[0003] In the prior art, although there are some attempts to improve the refractive index by modifying the resin material, there are often problems such as limited improvement in the refractive index, unstable material performance or complex preparation process. Therefore, it is necessary to provide a new technical solution to solve the above technical problems. Summary of the invention

[0004] The purpose of the present application is to provide a new technical solution for a resin material and a preparation method thereof, a preparation method of a resin wafer, optical products and electronic equipment.

[0005] In a first aspect, an embodiment of the present application provides a resin material, wherein the resin material comprises the following components:

[0006] Cycloolefin copolymer 100-120 parts;

[0007] 50-200 parts of inorganic nanoparticles;

[0008] 0.1-1 part of antioxidant;

[0009] 1 to 20 parts of toughening agent.

[0010] Optionally, the chemical formula of the cycloolefin copolymer is:

[0011]

[0012] Wherein, 0.1≤x / (x+y)≤0.9, 0.1≤y / (x+y)≤0.9, x and y are the numbers of monomers in the copolymer respectively, x and y are positive integers, k is 0 or 1, R1 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms or a cycloalkyl group bonded to R2 to form a ring, R2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms or a cycloalkyl group bonded to R1 to form a ring, and R3 is an alkyl group having 1 to 10 carbon atoms.

[0013] Optionally, the chemical formula of the cyclic olefin copolymer includes any one of the following:

[0014]

[0015] and

[0016]

[0017] Optionally, the raw materials for preparing the cycloolefin copolymer include at least a cycloolefin monomer and an α-olefin, and the cycloolefin monomer and the α-olefin are polymerized in a first solvent;

[0018] Wherein, the first solvent includes at least one of n-hexane, cyclohexane, cyclopentane, methylcyclohexane, benzene, toluene and xylene.

[0019] Optionally, the cycloolefin monomer and the α-olefin are polymerized under the catalytic action of a catalyst system;

[0020] The catalyst system includes a main catalyst and a co-catalyst;

[0021] The main catalyst includes a metallocene catalyst;

[0022] The cocatalyst includes methylaluminoxane MAO.

[0023] Optionally, the main catalyst includes at least one of Cp2ZrCl2, rac-[Et(Ind)2]ZrCl2, rac-[Et(Ind-H4)2]ZrCl2, rac-[Me2Si(Ind)2]ZrCl2, rac-[Ph2Si(Ind)2]ZrCl2, [Me2C(Flu)(Cp)]ZrCl2, [Me2Si(Flu)(3-tBuCp)]ZrCl2 and [Me2C(Flu)(3-tBuCp)]ZrCl2.

[0024] Optionally, the inorganic nanoparticles are at least one of TiO2 nanoparticles and ZrO2 nanoparticles.

[0025] Optionally, the antioxidant is a phosphite antioxidant;

[0026] The antioxidants include primary antioxidants and auxiliary antioxidants;

[0027] The primary antioxidant includes at least one of antioxidant 168 and antioxidant 626;

[0028] The auxiliary antioxidant includes at least one of antioxidant 1010 and antioxidant 1076

[0029] Optionally, the toughening agent is a thermoplastic elastomer toughening agent, and the toughening agent includes a polyolefin toughening agent or a styrene toughening agent.

[0030] Optionally, the refractive index of the resin material is greater than 1.7, and the glass transition temperature thereof is greater than or equal to 103°C.

[0031] In a second aspect, an embodiment of the present application provides a method for preparing a resin material, which is used to prepare the resin material as described in the first aspect, and the preparation method comprises:

[0032] Premixing the cycloolefin copolymer, the toughening agent, the antioxidant and the inorganic nanoparticles to obtain a mixture;

[0033] Dissolving the mixed material in a second solvent and stirring at a set temperature; wherein the second solvent includes toluene or ethyl acetate, and the set temperature is 50° C. to 80° C.;

[0034] After the second solvent is evaporated, the obtained solid product is dried to obtain a resin material; wherein the drying temperature is 50°C to 85°C.

[0035] Optionally, the preparation method of the cycloolefin copolymer comprises:

[0036] mixing a cyclic olefin monomer, an alpha olefin, and a first solvent;

[0037] A catalyst is added to carry out polymerization reaction to obtain a cycloolefin copolymer.

[0038] In a third aspect, an embodiment of the present application provides a method for preparing a resin wafer, the preparation method comprising:

[0039] Placing a resin material in a mold; wherein the resin material is the resin material described in the first aspect or the resin material prepared by the preparation method described in the second aspect;

[0040] The mold is placed in a vacuum oven, heated under negative pressure, and then opened after cooling to room temperature to obtain a resin sheet;

[0041] The resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

[0042] In a fourth aspect, an embodiment of the present application provides an optical product, wherein the optical product is made of the resin material according to the first aspect.

[0043] In a fifth aspect, an embodiment of the present application provides an electronic device, wherein the electronic device includes the optical product described in the fourth aspect.

[0044] One beneficial effect of this application is:

[0045] According to the resin material provided in one embodiment of the present application, by selecting cycloolefin copolymer (COC) as the main component and rationally proportioning inorganic nanoparticles, antioxidants and toughening agents, a substantial increase in the refractive index of the resin material is achieved while ensuring good processing performance and stability of the resin material.

[0046] Other features and advantages of the present specification will become apparent from the following detailed description of exemplary embodiments of the present specification with reference to the accompanying drawings. DETAILED DESCRIPTION

[0047] Various exemplary embodiments of the present application are now described in detail. It should be noted that the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present application unless otherwise specifically stated.

[0048] The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the present application, its application, or uses.

[0049] Techniques and equipment known to ordinary technicians in the relevant art may not be discussed in detail, but where appropriate, the techniques and equipment should be considered part of the specification.

[0050] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0051] The resin material and its preparation method, the preparation method of the resin wafer, the optical product and the electronic device provided in the embodiments of the present application are described in detail below in combination with specific embodiments.

[0052] According to one embodiment of the present application, a resin material is provided, wherein the resin material comprises the following components in parts by weight:

[0053] Cycloolefin copolymer 100-120 parts;

[0054] 50-200 parts of inorganic nanoparticles;

[0055] 0.1-1 part of antioxidant;

[0056] 1 to 20 parts of toughening agent.

[0057] The resin material provided in the embodiment of the present application can be used to manufacture, for example, optical waveguide sheets or other optical products such as optical lenses in the AR field.

[0058] The resin material provided in the embodiments of the present application has its components and the ratios between the components designed and optimized to achieve high refractive index, good processing performance, and stable physical and chemical properties.

[0059] The resin material provided in the embodiment of the present application is a composition, and its components mainly include the above-mentioned cycloolefin copolymer (COC), inorganic nanoparticles, antioxidants and toughening agents.

[0060] The cyclic olefin copolymer (COC): as a main component of the resin material of the present application, the cyclic olefin copolymer (COC) has excellent light transmittance and good processing performance.

[0061] By selecting a cycloolefin copolymer with a specific structure, it can be ensured that the final resin material has excellent basic properties, providing a basis for further improving the refractive index and other properties of the resin material.

[0062] The inorganic nanoparticles in the resin material of the present application mainly play a role in increasing the refractive index. Specifically, by adding 50 to 200 parts of inorganic nanoparticles to the components of the resin material, the refractive index of the resin material can be significantly increased to reach or exceed the requirement of 1.7. For most resin materials, the refractive index is relatively low, and reaching 1.7 is a relatively high refractive index.

[0063] However, it should be noted that the more inorganic nanoparticles are added, the better. Excessive addition may cause the transmittance and processing performance of the formed resin material to decrease. Therefore, the addition amount range of inorganic nanoparticles is designed in this application to ensure that the refractive index is increased while maintaining the stability of other properties.

[0064] The antioxidant: In the present application, the antioxidant is mainly used to prevent the resin material from turning yellow due to oxidation during use.

[0065] Specifically, in the components of the present application, by adding 0.1 to 1 part of antioxidant, the antioxidant performance of the resin material can be effectively improved and its service life can be extended. At the same time, the amount of antioxidant added has also been carefully formulated to ensure that while preventing the resin material from yellowing, it will not significantly reduce the visible light transmittance of the material and increase the haze of the resin material.

[0066] The toughening agent is mainly used to increase the toughness of the resin material, and when used to make optical products, it can make the optical products more durable.

[0067] Specifically, by adding 1 to 20 parts of toughening agent to the components of the present application, the toughness of the resin material can be significantly improved, making it less likely to break. At the same time, the amount of toughening agent added has also been optimized to ensure that while increasing the toughness, the mechanical strength and refractive index of the resin material will not be significantly reduced.

[0068] The resin material provided in the embodiment of the present application effectively improves the refractive index of the resin material by selecting a combination of cycloolefin copolymer (COC) and inorganic nanoparticles in a specific proportion, so that it can meet the demand for high refractive index in the field of AR diffraction optical waveguides, and the refractive index can reach above 1.7.

[0069] The resin material of the present application has good processing performance and stability through reasonable formula design while ensuring a high refractive index. For example, the addition of a toughening agent enhances the toughness of the resin material, making it less likely to break. The addition of an antioxidant effectively improves the anti-oxidation performance of the resin material and prolongs its service life.

[0070] Compared with traditional glass materials, the resin material provided in this application has low density and light weight, which helps to meet the lightweight requirements of products, reduce costs and improve the market competitiveness of products.

[0071] The resin material of the present application not only has a greatly improved refractive index, but also performs well in multiple performance indicators such as visible light transmittance and glass transition temperature (Tg), and can fully meet the requirements for high-performance optical materials in the field of AR diffraction optical waveguides, for example.

[0072] In some examples of the present application, the chemical formula of the cyclic olefin copolymer is:

[0073]

[0074] Wherein, 0.1≤x / (x+y)≤0.9, 0.1≤y / (x+y)≤0.9, x and y are the numbers of monomers in the copolymer respectively, x and y are positive integers, k is 0 or 1, R1 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms or a cycloalkyl group bonded to R2 to form a ring, R2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms or a cycloalkyl group bonded to R1 to form a ring, and R3 is an alkyl group having 1 to 10 carbon atoms.

[0075] In this example of the present application, the chemical formula of the cycloolefin copolymer shows its molecular structure, and the cycloolefin copolymer includes different functional groups and connection modes. By adjusting the ratio of x and y, the composition and properties of the cycloolefin copolymer can be changed, thereby achieving the regulation of the properties of the formed resin material.

[0076] By using the cycloolefin copolymer provided in this example of the present application as the main component of the resin material, the refractive index of the resin material can be significantly improved. This is because the cycloolefin copolymer itself has a high refractive index, and its refractive index performance can be further optimized through specific structural design and synthesis methods.

[0077] The cycloolefin copolymer provided in this example of the present application has good processing properties, such as melt fluidity, thermal stability and moldability, etc. These properties make the resin material easy to operate and control during processing, which helps to improve the yield and quality of the product.

[0078] The cycloolefin copolymer provided in this example of the present application has stable physical and chemical properties, such as weather resistance, chemical corrosion resistance, heat resistance, etc. These properties enable the resin material to maintain stable performance during use and extend its service life.

[0079] By properly mixing the cyclic olefin copolymer shown in this example of the present application with other components such as inorganic nanoparticles, antioxidants and toughening agents, the comprehensive properties of the resin material can be optimized.

[0080] According to the cycloolefin copolymer provided in this example of the present application, by using it as the main component of the resin material, the finally obtained resin material has excellent comprehensive properties, and therefore has broad application prospects in the fields of AR diffraction optical waveguides, etc.

[0081] For example, the resin material of the present application can be used as a high-performance optical element material to manufacture optical devices with high refractive index, high transmittance and low loss.

[0082] In some examples of the present application, the chemical formula of the cyclic olefin copolymer includes any one of the following:

[0083]

[0084]

[0085] and

[0086]

[0087] The cycloolefin copolymer (COC) used in this example of the present application has a specific chemical structure, and these structures are preferably the above-mentioned chemical formula (I) and chemical formula (V).

[0088] Chemical formula (I) to chemical formula (II): Both of them present a monocyclic structure. In these two chemical formulas, R1 and R2 are both hydrogen atoms, indicating that the specific part of these cycloolefin copolymers does not have other substituents or complex cyclic structures. The monomers without rings in these two chemical formulas are relatively simple. For example, in chemical formula (I) and chemical formula (II), these monomers are ethylene monomers. Ethylene has a simple double bond structure and is easy to participate in copolymerization reactions.

[0089] Chemical formulas (III) to (V): These three present a double ring structure, which may have higher molecular rigidity and refractive index than a single ring structure. Similarly, R1 and R2 in these three chemical formulas are also hydrogen atoms, indicating that the specific parts of these cycloolefin copolymers remain simple. The monomers without rings in these three chemical formulas are ethylene monomers or propylene monomers. Ethylene has a simple double bond structure and is easy to participate in copolymerization reactions. Propylene has a methyl side chain, which may introduce additional intermolecular interactions into the copolymer, thereby affecting its physical properties.

[0090] The chemical formulas of the five cycloolefin copolymers provided in this example of the present application have the following advantages:

[0091] (1) Simple preparation of raw materials: The raw materials (such as ethylene and propylene) on which these chemical formulas are based are olefin monomers, which are easily available and relatively low in cost.

[0092] (2) Easy to synthesize: These raw materials can be easily introduced into molecular chains during copolymerization reactions, thereby synthesizing high-yield cycloolefin copolymers.

[0093] (3) Superior performance: Since these cycloolefin copolymers have a specific chemical structure, they may exhibit excellent physical properties, such as high refractive index, good transparency and stability, etc. These properties make them have great application value in the field of high refractive index resin materials.

[0094] In some examples of the present application, the raw materials for preparing the cycloolefin copolymer include at least cycloolefin monomers and α-olefins, and the cycloolefin monomers and the α-olefins are polymerized in a first solvent; wherein the first solvent includes at least one of n-hexane, cyclohexane, cyclopentane, methylcyclohexane, benzene, toluene and xylene.

[0095] In the example of the present application, the raw materials for preparing the cycloolefin copolymer include at least cycloolefin monomer and α-olefin, and the two raw materials undergo polymerization reaction in a first solvent. The first solvent here can be at least one of n-hexane, cyclohexane, cyclopentane, methylcyclohexane, benzene, toluene and xylene.

[0096] Among them, the material selection of the first solvent should have the following important technical effects:

[0097] Good solubility: The selected solvent can effectively dissolve the raw materials (i.e. cycloolefin monomers and α-olefins) and catalysts, which is the prerequisite for ensuring the smooth progress of the polymerization reaction. Good solubility helps the reactants to fully contact and mix, thereby improving the efficiency of the polymerization reaction and the uniformity of the product.

[0098] Good stability: Under the polymerization conditions, the selected solvent type will not undergo physical and chemical reactions, which helps to maintain the stability of the entire reaction system. A first solvent with good stability can avoid adverse effects on the polymerization reaction, such as initiating side reactions or causing product degradation.

[0099] Immiscible with water: Since some catalysts (such as methylaluminoxane MAO) become ineffective when exposed to water, the first solvent selected needs to be immiscible with water. This property helps protect the activity of the catalyst and ensures that the polymerization reaction proceeds as expected.

[0100] In addition, the first solvent selected in this example of the present application is easily available on the market, which helps to reduce production costs and improve production efficiency.

[0101] In this example of the present application, the solvent is carefully selected to ensure that the preparation process of the cycloolefin copolymer is efficient, stable and controllable. This not only helps to improve the quality and performance of the product, but also helps to reduce production costs and promote the industrial application of related technologies.

[0102] In this example of the present application, the raw material for preparing the cyclic olefin copolymer includes α-olefin.

[0103] When the α-olefin participates in the polymerization reaction in gaseous form, the cycloolefin monomer needs to be mixed with the first solvent first, and then the gaseous α-olefin is introduced for polymerization. The gaseous α-olefin is more easily evenly distributed in the reaction system, which is conducive to obtaining a uniform polymer structure. The gaseous form is convenient for controlling the ratio of reactants and the reaction rate.

[0104] When the α-olefin is in liquid form, it can be directly mixed with the cycloolefin monomer and the first solvent, and then the temperature is raised and a catalyst is added to carry out polymerization. The addition of liquid α-olefin is relatively simple and does not require additional gas processing equipment. Liquid α-olefin is more likely to form a uniform solution with the cycloolefin monomer and the first solvent, which is conducive to the polymerization reaction.

[0105] It should be noted that the resin material of the present application, whether to choose gaseous or liquid α-olefin, depends on the specific production process, equipment conditions, cost control and performance requirements of the desired polymer.

[0106] In some examples of the present application, the cycloolefin monomer and the α-olefin are polymerized under the catalytic action of a catalyst system; wherein the catalyst system includes a main catalyst and a co-catalyst; the main catalyst includes a metallocene catalyst, and the co-catalyst includes methylaluminoxane MAO.

[0107] In the example of the present application, the cycloolefin monomer and the α-olefin are polymerized under the catalytic action of a catalyst system, wherein the catalyst system is composed of a main catalyst and a co-catalyst. The main catalyst is a metallocene catalyst, and the co-catalyst is methylaluminoxane (MAO). The selection of the catalyst system in the present application has significant technical effects, which are specifically analyzed as follows:

[0108] (1) High activity: Metallocene catalysts are known for their high activity and can achieve efficient polymerization reactions at lower temperatures and pressures. This helps reduce energy consumption and production costs while improving production efficiency. When metallocene catalysts are used in combination with methylaluminoxane (MAO), their activity can be further enhanced, thereby accelerating the polymerization process.

[0109] (2) The entire catalytic system is stable and the reaction is controllable: The catalytic system composed of metallocene catalyst and methylaluminoxane (MAO) has high stability and can maintain activity during the reaction. This helps to achieve controllability of the polymerization reaction and ensure that the polymerization reaction proceeds as expected. At the same time, a stable catalytic system also helps to reduce the occurrence of side reactions and improve the purity and quality of the product.

[0110] In some examples of the present application, the main catalyst includes at least one of Cp2ZrCl2, rac-[Et(Ind)2]ZrCl2, rac-[Et(Ind-H4)2]ZrCl2, rac-[Me2Si(Ind)2]ZrCl2, rac-[Ph2Si(Ind)2]ZrCl2, [Me2C(Flu)(Cp)]ZrCl2, [Me2Si(Flu)(3-tBuCp)]ZrCl2 and [Me2C(Flu)(3-tBuCp)]ZrCl2.

[0111] The metallocene catalysts in this example of the present application have high catalytic activity and can achieve efficient polymerization reactions at lower temperatures and pressures, thereby improving production efficiency. In addition, the metallocene catalysts have a single active center, which makes the polymerization reaction more controllable and the structure and properties of the polymer more uniform.

[0112] In some examples of the present application, the inorganic nanoparticles are at least one of TiO2 nanoparticles and ZrO2 nanoparticles.

[0113] In this example of the present application, the inorganic nanoparticles are at least one of TiO2 nanoparticles and ZrO2 nanoparticles. This choice has a significant technical effect on the preparation of high refractive index resin materials, and the following is a detailed analysis of this.

[0114] About the characteristics of inorganic nanoparticles:

[0115] (1) High refractive index: TiO2 nanoparticles and ZrO2 nanoparticles are both materials with high refractive index. Adding them as inorganic nanoparticles to the components of the resin material can effectively increase the refractive index of the resin material, thereby meeting the demand for high refractive index materials in fields such as AR diffraction waveguides.

[0116] (2) Good stability: TiO2 nanoparticles and ZrO2 nanoparticles have good stability in the resin, are not prone to agglomeration or sedimentation, and can maintain the uniformity of the resin material performance.

[0117] (3) Good optical properties: These two types of nanoparticles have high transmittance to visible light and can reduce the haze of the material and improve the optical properties.

[0118] According to this example of the present application, by adding TiO2 nanoparticles or ZrO2 nanoparticles to the components of the resin material, the refractive index of the resin material can be significantly increased to reach or exceed 1.7, meeting the needs of application fields such as AR.

[0119] The addition of TiO2 nanoparticles and ZrO2 nanoparticles not only increases the refractive index, but also maintains or increases the visible light transmittance of the material and reduces the haze, thereby optimizing the optical performance.

[0120] In addition, these inorganic nanoparticles in this example of the present application can also enhance the mechanical properties, heat resistance, etc. of the resin material, thereby improving the overall performance of the resin material.

[0121] In some examples of the present application, the antioxidant is a phosphite antioxidant; the antioxidant includes a primary antioxidant and an auxiliary antioxidant; the primary antioxidant includes at least one of antioxidant 168 and antioxidant 626; the auxiliary antioxidant includes at least one of antioxidant 1010 and antioxidant 1076.

[0122] In this example of the present application, the antioxidant is a phosphite antioxidant, and it is pointed out that the main antioxidant is, for example, at least one of antioxidant 168 and antioxidant 626, and the auxiliary antioxidant is, for example, at least one of antioxidant 1010 and antioxidant 1076. This selection has a significant technical effect on improving the antioxidant performance of the resin material.

[0123] Phosphite antioxidants: This type of antioxidant has highly efficient antioxidant properties and can capture free radicals generated by resin materials during processing and use, preventing oxidative degradation of resin materials.

[0124] Synergistic effect of primary antioxidant and auxiliary antioxidant: The primary antioxidant (such as antioxidant 168 and antioxidant 626) is mainly responsible for capturing peroxyl radicals, while the auxiliary antioxidant (such as antioxidant 1010 and antioxidant 1076) can decompose hydroperoxides. The synergistic effect of the two can more effectively improve the antioxidant properties of resin materials.

[0125] Good compatibility: The antioxidants mentioned in this example of the present application have good compatibility with the resin material and can be evenly dispersed in the resin material to ensure that the antioxidant effect is fully exerted.

[0126] In the present application, by adding phosphite antioxidants to the components of the resin material, especially the combination of a primary antioxidant and an auxiliary antioxidant, the antioxidant properties of the resin material can be significantly improved and the service life of the material can be extended.

[0127] The addition of antioxidants helps maintain the stability of the performance of resin materials and prevent performance degradation caused by oxidative degradation, such as yellowing of the resin material and reduction of mechanical properties.

[0128] When the antioxidant is added in an appropriate amount, it can effectively balance the antioxidant properties and visible light transmittance of the resin material, reduce the haze, and maintain the optical properties of the resin material.

[0129] In some examples of the present application, the toughening agent is a thermoplastic elastomer toughening agent, and the toughening agent includes a polyolefin toughening agent or a styrene toughening agent.

[0130] In this example of the present application, the toughening agent is a thermoplastic elastomer toughening agent, and specifically includes a polyolefin toughening agent and a styrene toughening agent. This selection is intended to optimize the overall performance of the formed resin material by improving the toughness of the material.

[0131] It should be noted that thermoplastic elastomer toughening agents are a type of material that has rubber elasticity and thermoplastic processability. They can exhibit rubber-like elasticity at room temperature and can be processed like thermoplastics at high temperatures.

[0132] Polyolefin toughening agents have good compatibility with cycloolefin copolymer COC and can be effectively dispersed in resin materials to form a uniform toughening effect.

[0133] Styrene tougheners also have excellent toughening effects and can provide better processing performance and appearance in some cases. They can also improve the toughness of the material to a certain extent.

[0134] In the components of the resin material provided in the embodiments of the present application, by adding a polyolefin toughening agent or a styrene toughening agent, the toughness of the resin material can be significantly improved, so that the resin material can better absorb energy when subjected to impact or external force, and is not easy to crack or break.

[0135] In some examples of the present application, the refractive index of the resin material is greater than 1.7, and the glass transition temperature thereof is greater than or equal to 103°C.

[0136] The refractive index is a measure of a material's ability to refract light. For optical applications such as AR diffractive waveguides, a high refractive index is a key factor in achieving efficient light transmission and focusing.

[0137] In the present application, by increasing the refractive index of the resin material to above 1.7, the optical performance of, for example, AR devices, such as image clarity and brightness, can be significantly improved, thereby enhancing the user experience.

[0138] Glass transition temperature (Tg) is the temperature at which a polymer changes from a glassy state to a highly elastic state, which reflects the thermal stability and operating temperature range of the material. For optical components such as AR diffractive waveguides, the material needs to be able to withstand certain temperature and pressure changes without deformation or performance degradation.

[0139] The glass transition temperature of the resin material of the present application is greater than or equal to 103° C., which can ensure that the high-refractive-index resin material maintains stable performance within a wide temperature range, thereby adapting to various complex application environments.

[0140] According to another embodiment of the present application, a method for preparing a resin material is provided, for preparing the resin material as described above, the method comprising the following steps S1 to S3:

[0141] Step S1, premixing the cycloolefin copolymer, toughening agent, antioxidant and inorganic nanoparticles to obtain a mixture;

[0142] Step S2, dissolving the mixture in a second solvent and stirring at a set temperature; wherein the second solvent includes toluene or ethyl acetate, and the set temperature is 50° C. to 80° C.;

[0143] Step S3, after evaporating the second solvent, drying the obtained solid product to obtain a resin material; wherein the drying temperature is 50°C to 85°C.

[0144] In the above step S1: by weight, the cycloolefin copolymer is 100 to 120 parts by weight, the inorganic nanoparticles are 50 to 200 parts by weight, the antioxidant is 0.1 to 1 part by weight, and the toughening agent is 1 to 20 parts by weight. In the step S1, the above four components need to be weighed according to the preset weight parts and preliminarily premixed so that the components can be mixed with each other.

[0145] In the above step S2, the mixture obtained in step S1 is dissolved in an appropriate amount of a second solvent, which can be, for example, toluene. The entire dissolution process is carried out under a set temperature condition, which should not be too high, for example, it can be between 50°C and 80°C, and the more suitable temperature is 60°C, and it is necessary to ensure that the temperature does not exceed 80°C to avoid denaturation or degradation of components due to excessive temperature. At a constant temperature, continuous stirring is performed for 2 to 4 hours until all components are completely dissolved and a uniform solution is formed.

[0146] Next, in the above step S3, for example, a rotary evaporator can be used to perform a second solvent evaporation treatment on the solution obtained in step S2 to remove toluene therein, thereby obtaining a pure solid product. In this step, care must be taken to avoid introducing impurities during the evaporation process.

[0147] In step S3, the solid product is collected and placed in a container, and then sent to a vacuum oven for further drying. For example, the solid product may be dried in a vacuum environment for more than 12 hours at a constant temperature of 60°C to ensure that the moisture and residual solvent inside it are completely removed, thereby achieving the best physical and chemical properties. It should also be noted that the temperature during the entire drying process must be strictly controlled below 85°C to prevent the resin from undergoing adverse changes due to overheating.

[0148] The preparation method of the resin material provided in the embodiment of the present application, through accurate component ratio and premixing step, ensures the uniform distribution of each component in the resin material, which is very important for improving the overall performance and stability of the resin. Dissolving at a suitable temperature not only accelerates the dissolution process, but also ensures the full dissolution of each component, thereby improving the preparation efficiency of the resin. By the method combined with rotary evaporation and vacuum drying, the solvent in the resin can be efficiently removed, avoiding the adverse effects of solvent residue on resin performance. Controlling the temperature during dissolution and drying avoids the denaturation or degradation of the resin component caused by excessive temperature, thereby ensuring the excellent performance of the resin.

[0149] The preparation method of the resin material provided in the embodiment of the present application is simple, easy to control, and can realize mass production. The prepared resin material has excellent physical and chemical properties, such as high refractive index, good thermal stability and processing performance, which is of great significance for meeting the demand for high-performance resin materials (resin wafers) in fields such as AR diffraction optical waveguides.

[0150] In some examples of the present application, the method for preparing the cyclic olefin copolymer comprises the following steps:

[0151] mixing a cyclic olefin monomer, an alpha olefin, and a first solvent;

[0152] A catalyst is added to carry out polymerization reaction to obtain a cycloolefin copolymer.

[0153] In this example of the present application, the preparation method of the cycloolefin copolymer includes two main steps: mixing a cycloolefin monomer, an α-olefin and a first solvent and adding a catalyst for polymerization to obtain a cycloolefin copolymer. The first solvent includes at least one of n-hexane, cyclohexane, cyclopentane, methylcyclohexane, benzene, toluene and xylene.

[0154] In this example of the present application, the raw material for preparing the cyclic olefin copolymer includes α-olefin.

[0155] When the α-olefin participates in the polymerization reaction in gaseous form, it is necessary to first mix the cycloolefin monomer and the first solvent, and then introduce the gaseous α-olefin to carry out polymerization.

[0156] Gaseous α-olefins are more easily evenly distributed in the reaction system, which is conducive to obtaining a more uniform polymer structure. The gaseous form makes it easier to control the ratio of reactants and the reaction rate.

[0157] When the α-olefin is in liquid form, it can be directly mixed with the cycloolefin monomer and the first solvent, and then heated and a catalyst is added to carry out polymerization.

[0158] The addition of liquid α-olefin is relatively simple and does not require additional gas processing equipment. Liquid α-olefin is more likely to form a uniform solution with the cycloolefin monomer and the first solvent, which is beneficial to the polymerization reaction.

[0159] It should be noted that the resin material of the present application, whether to choose gaseous or liquid α-olefin, depends on the specific production process, equipment conditions, cost control and performance requirements of the desired polymer.

[0160] According to another embodiment of the present application, a method for preparing a resin wafer is provided, the method comprising the following steps S100 to S300:

[0161] Step S100, placing a resin material in a mold; wherein the resin material is the resin material as described above or a resin material prepared by the method for preparing the resin material as described above;

[0162] Step S200, placing the mold in step S100 in a vacuum oven, heating it under negative pressure, and then cooling it to room temperature and opening the mold to obtain a resin sheet;

[0163] Step S300, slicing, grinding, cleaning and annealing the resin sheet obtained in step S300 to obtain a resin wafer.

[0164] In the above step S100: the resin material is the resin material as described above, which has cycloolefin copolymer (COC) as a main component and is added with toughening agent, antioxidant and inorganic nanoparticles.

[0165] The mold is used to mold the resin material so that it has a desired shape and size. When preparing a resin wafer, the shape and size of the mold should meet the production requirements of the wafer.

[0166] In the above step S200: the mold is placed in a vacuum oven, heated under negative pressure, and then cooled to room temperature before opening the mold to obtain a resin sheet. The vacuum oven provides an oxygen-free, dust-free heating environment, which helps to prevent oxidation or contamination of the resin material during the heating process. The negative pressure state helps to eliminate bubbles in the mold and the resin material, and improve the quality of the finished resin wafer. Heating softens the resin material and fills the mold, while cooling solidifies and shapes the resin material. These two processes together determine the shape, size and performance of the resin wafer.

[0167] After cooling to room temperature, the mold can be opened and the solidified resin sheet can be taken out.

[0168] In the above step S300: the obtained resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

[0169] In terms of term, slicing is to cut the resin sheet into wafers with the desired thickness and size. Polishing is to polish the wafer to remove surface defects and uneven parts to improve the smoothness and flatness of the wafer. Cleaning is to clean the wafer to remove surface stains and impurities to ensure the cleanliness of the wafer. Annealing helps to eliminate stress and defects inside the wafer and improve its stability and reliability. At the same time, annealing can further improve the optical and mechanical properties of the wafer.

[0170] It should be noted that the resin wafer can be used to make optical elements such as optical waveguides and lenses.

[0171] The present application also provides an optical product, which can be prepared from the above-mentioned resin material. Since the resin material of the present application has the optical property of high refractive index, the optical product of the present application also has the same advantages, which will not be described in detail here.

[0172] The embodiment of the present application also provides an electronic device, the electronic device comprising the above optical product. Since the optical product has good optical properties, the electronic device also has the same advantages, which will not be described in detail here.

[0173] The present application is further described below in conjunction with specific embodiments 1 to 5.

[0174] Example 1

[0175] Premixing cycloolefin copolymer, polyolefin toughening agent, antioxidant and nano-TiO2 to obtain a mixture; wherein the cycloolefin copolymer is 100 parts by weight; the polyolefin toughening agent is 10 parts by weight; the antioxidant includes antioxidant 1010 and antioxidant 168, and the antioxidant is 0.2 parts by weight; the nano-TiO2 is 60 parts by weight;

[0176] The chemical formula of the cycloolefin copolymer is:

[0177]

[0178] The mixture was dissolved in toluene and stirred at 60°C;

[0179] After the toluene is evaporated, the obtained solid product is dried to obtain a resin material; wherein the drying temperature is, for example, 60° C. and the drying time is 12 hours;

[0180] The resin material is placed in a mold; the mold is then placed in a vacuum oven, heated under negative pressure, and then opened after cooling to room temperature to obtain a resin sheet; finally, the resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

[0181] Example 2

[0182] Premixing cycloolefin copolymer, polyolefin toughening agent, antioxidant and nano-TiO2 to obtain a mixture; wherein the cycloolefin copolymer is 100 parts by weight; the polyolefin toughening agent is 20 parts by weight; the antioxidant includes antioxidant 1010 and antioxidant 168, and the antioxidant is 0.2 parts by weight; the nano-TiO2 is 60 parts by weight;

[0183] The chemical formula of the cycloolefin copolymer is:

[0184]

[0185] The mixture was dissolved in toluene and stirred at 60°C;

[0186] After the toluene is evaporated, the obtained solid product is dried to obtain a resin material; wherein the drying temperature is, for example, 60° C. and the drying time is 12 hours;

[0187] The resin material is placed in a mold; the mold is then placed in a vacuum oven, heated under negative pressure, and then opened after cooling to room temperature to obtain a resin sheet; finally, the resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

[0188] Example 3

[0189] Premixing cycloolefin copolymer, polyolefin toughening agent, antioxidant and nano-TiO2 to obtain a mixture; wherein the cycloolefin copolymer is 100 parts by weight; the polyolefin toughening agent is 10 parts by weight; the antioxidant includes antioxidant 1010 and antioxidant 168, and the antioxidant is 0.2 parts by weight; the nano-TiO2 is 60 parts by weight;

[0190] The chemical formula of the cycloolefin copolymer is:

[0191]

[0192] The mixture was dissolved in toluene and stirred at 60°C;

[0193] After the toluene is evaporated, the obtained solid product is dried to obtain a resin material; wherein the drying temperature is, for example, 60° C. and the drying time is 12 hours;

[0194] The resin material is placed in a mold; the mold is then placed in a vacuum oven, heated under negative pressure, and then opened after cooling to room temperature to obtain a resin sheet; finally, the resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

[0195] Example 4

[0196] Premixing cycloolefin copolymer, polyolefin toughening agent, antioxidant and nano-TiO2 to obtain a mixture; wherein the cycloolefin copolymer is 100 parts by weight; the polyolefin toughening agent is 10 parts by weight; the antioxidant includes antioxidant 1010 and antioxidant 168, and the antioxidant is 0.2 parts by weight; the nano-TiO2 is 60 parts by weight;

[0197] The chemical formula of the cycloolefin copolymer is:

[0198]

[0199] The mixture was dissolved in toluene and stirred at 60°C;

[0200] After the toluene is evaporated, the obtained solid product is dried to obtain a resin material; wherein the drying temperature is, for example, 60° C. and the drying time is 12 hours;

[0201] The resin material is placed in a mold; the mold is then placed in a vacuum oven, heated under negative pressure, and then opened after cooling to room temperature to obtain a resin sheet; finally, the resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

[0202] Example 5

[0203] Premixing cycloolefin copolymer, polyolefin toughening agent, antioxidant and nano-TiO2 to obtain a mixture; wherein the cycloolefin copolymer is 100 parts by weight; the polyolefin toughening agent is 10 parts by weight; the antioxidant includes antioxidant 1010 and antioxidant 168, and the antioxidant is 0.2 parts by weight; the nano-TiO2 is 120 parts by weight;

[0204] The chemical formula of the cycloolefin copolymer is:

[0205]

[0206] The mixture was dissolved in toluene and stirred at 60°C;

[0207] After the toluene is evaporated, the obtained solid product is dried to obtain a resin material; wherein the drying temperature is, for example, 60° C. and the drying time is 12 hours;

[0208] The resin material is placed in a mold; the mold is then placed in a vacuum oven, heated under negative pressure, and then opened after cooling to room temperature to obtain a resin sheet; finally, the resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

[0209] According to the above-mentioned embodiments 1 to 5, the resin wafers obtained have the following properties:

[0210] The refractive index is greater than 1.7, the visible light transmittance is ≥87.5%, the thickness uniformity is ≤5nm, the stress (birefringence) is ≤5nm, the haze is ≤0.1%, the roughness is ≤0.5nm, the flatness is <25μm, the glass transition temperature Tg is ≥103℃, etc.

[0211] The above embodiments focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.

[0212] Although some specific embodiments of the present application have been described in detail by way of example, it should be understood by those skilled in the art that the above examples are only for illustration, not for limiting the scope of the present application. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present application. The scope of the present application is defined by the appended claims.

Claims

1. A resin material, characterized in that: By weight, it includes the following components: Cycloolefin copolymer 100-120 parts; 50-200 parts of inorganic nanoparticles; 0.1-1 part of antioxidant; 1 to 20 parts of toughening agent.

2. The resin material according to claim 1, characterized in that The chemical formula of the cycloolefin copolymer is: Wherein, 0.1≤x / (x+y)≤0.9, 0.1≤y / (x+y)≤0.9, x and y are the numbers of monomers in the copolymer respectively, x and y are positive integers, k is 0 or 1, R1 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms or a cycloalkyl group bonded to R2 to form a ring, R2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms or a cycloalkyl group bonded to R1 to form a ring, and R3 is an alkyl group having 1 to 10 carbon atoms.

3. The resin material according to claim 2, characterized in that The chemical formula of the cyclic olefin copolymer includes any one of the following:

4. The resin material according to any one of claims 1 to 3, characterized in that: The raw materials for preparing the cycloolefin copolymer at least include cycloolefin monomer and α-olefin, and the cycloolefin monomer and the α-olefin are polymerized in a first solvent; Wherein, the first solvent includes at least one of n-hexane, cyclohexane, cyclopentane, methylcyclohexane, benzene, toluene and xylene.

5. The resin material according to claim 4, characterized in that The cycloolefin monomer and the α-olefin are polymerized under the catalytic action of a catalyst system; The catalyst system includes a main catalyst and a co-catalyst; The main catalyst includes a metallocene catalyst; The cocatalyst includes methylaluminoxane MAO.

6. The resin material according to claim 5, characterized in that The main catalyst includes at least one of Cp2ZrCl2, rac-[Et(Ind)2]ZrCl2, rac-[Et(Ind-H4)2]ZrCl2, rac-[Me2Si(Ind)2]ZrCl2, rac-[Ph2Si(Ind)2]ZrCl2, [Me2C(Flu)(Cp)]ZrCl2, [Me2Si(Flu)(3-tBuCp)]ZrCl2 and [Me2C(Flu)(3-tBuCp)]ZrCl2.

7. The resin material according to claim 1, characterized in that The inorganic nanoparticles are at least one of TiO2 nanoparticles and ZrO2 nanoparticles.

8. The resin material according to claim 1, characterized in that The antioxidant is a phosphite antioxidant; The antioxidants include primary antioxidants and auxiliary antioxidants; The primary antioxidant includes at least one of antioxidant 168 and antioxidant 626; The auxiliary antioxidant includes at least one of antioxidant 1010 and antioxidant 1076 .

9. The resin material according to claim 1, characterized in that The toughening agent is a thermoplastic elastomer toughening agent, and the toughening agent includes a polyolefin toughening agent or a styrene toughening agent.

10. The resin material according to claim 1, characterized in that The resin material has a refractive index greater than 1.7 and a glass transition temperature greater than or equal to 103°C.

11. A method for preparing a resin material, characterized in that: For preparing the resin material according to any one of claims 1 to 10, the preparation method comprising: Premixing the cycloolefin copolymer, the toughening agent, the antioxidant and the inorganic nanoparticles to obtain a mixture; Dissolving the mixed material in a second solvent and stirring at a set temperature; wherein the second solvent includes toluene or ethyl acetate, and the set temperature is 50° C. to 80° C.; After the second solvent is evaporated, the obtained solid product is dried to obtain a resin material; wherein the drying temperature is 50°C to 85°C.

12. The preparation method according to claim 11, characterized in that: The preparation method of the cycloolefin copolymer comprises: mixing a cyclic olefin monomer, an alpha olefin, and a first solvent; A catalyst is added to carry out polymerization reaction to obtain a cycloolefin copolymer.

13. A method for preparing a resin wafer, characterized in that: include: Placing a resin material in a mold; wherein the resin material is the resin material according to any one of claims 1 to 10 or the resin material prepared by the preparation method according to claim 11 or 12; The mold is placed in a vacuum oven, heated under negative pressure, and then opened after cooling to room temperature to obtain a resin sheet; The resin sheet is sliced, polished, cleaned and annealed to obtain a resin wafer.

14. An optical product, characterized in that: The optical product is made of the resin material according to any one of claims 1 to 11.

15. An electronic device, characterized in that: The optical product comprising the invention described in claim 14.

Citation Information

Patent Citations

  • Composition for optical material

    JP2008024735A

Cited By

  • Preparation method of modified cycloolefin copolymer and application of modified cycloolefin copolymer in curved screen

    CN120590736A